PEMBUATAN SWEET POTATO POWDER SEBAGAI SOLUSI DIVERSIFIKASI PANGAN DAN MENURUNKAN DIABETES MELITUS (SEBUAH HASIL KARYA KEWIRAUSAHAAN PROYEK P5 KURIKULUM MERDEKA) - Sanjaya, Ari; Asyara, Tasya; Fadhilah, Cherya Koukla; Safitri, Yulia; Lestari, Yuni Selvi (Journal of Chemistry Education and Integration, 2024)
AbstractProduction sweet potato in Indonesia is almost 90% used as food with a consumption rate of 6.6 kg / year. Sweet potatoes can reduce blood sugar levels of people with diabetes mellitus. Diabetes Mellitus is one of the non-communicable diseases that has become a world health problem. The purpose of this study was to find out how to make sweet potato powder, be used as a food diversification solution, and reduce diabetes mellitus. This research method is to use experimental methods. The results of this study are purple sweet potatoes can be used as flour to help reduce sugar levels in diabetics militus, and food diversification solutions such as being a mixture in making pudding, biscuits, noodles, ice cream and others. Keywords: Sweet Potato Powder, Diversification, and Diabetes Mellitus